THE INFLUENCE OF DIGITAL LITERACY AND DIGITAL WORKPLACE ON E-LEADERSHIP OF EDUCATORS AND EDUCATION STAFF OF A STATE VOCATIONAL SCHOOL - Adri Daswin; Mahdum Mahdum; Hadriana Hadriana (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2022)
The development of information and communication technology has influenced the current leadership style. Leadership not only can be implemented face-to-face, but can also be done through the use of electronic devices and the internet, which is called e-leadership. This study aims to obtain an empirical picture about the influence of digital literacy and digital workplace on e-leadership of educators and education staff of State Vocational Schools 5 Pekanbaru – Riau, either partially or simultaneously. This research was conducted from January to June 2022, but the data was collected in March 2022. The research instrument was a questionnaire given to 95 educators and education staff selected as the samples. The obtained data then analyzed through descriptive statistics and inferential statistics. The results of data analysis show that digital literacy has a significant influence as many as 30% on e-leadership and the digital workplace has a significant influence as many as 47.1% on e-leadership. Simultaneously digital literacy and digital workplace influence as many as 32%. on e-leadership. This implies that it is necessary to improve the digital literacy and digital workplace skills of educators and education staff of State Vocational Schools 5 Pekanbaru – Riau to improve their e-leadership skills